2012
DOI: 10.1080/17480272.2012.694909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steam injection re-drying of Japanese cedar on preservative leaching after passive impregnation

Abstract: This study investigated the effects of steam injection re-drying on the leaching of copper azole type B (CAz-B) preservative from green and kiln dried Japanese cedar (Cryptomeria japonica (L.f.) D.Don) lumber treated by the passive impregnation method. The leaching and fungal treatments were performed according to the JIS Z 2101-1994 standard. Sixteen hours of steam injection re-drying reduced the moisture content from 152 to 82% and 195 to 55% for initially green and dry lumber, respectively. Preservative ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…As reported by Ando et al (2012), minute surface cracking and slight darkening were observed when Japanese cedar specimens were dried by superheated steam after preservative impregnation. Surface cracking during drying is common for Japanese cedar lumber (Nakada et al 1998), and kiln drying of this lumber is a problem facing the Japanese wood industry (Obataya et al 2006).…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…As reported by Ando et al (2012), minute surface cracking and slight darkening were observed when Japanese cedar specimens were dried by superheated steam after preservative impregnation. Surface cracking during drying is common for Japanese cedar lumber (Nakada et al 1998), and kiln drying of this lumber is a problem facing the Japanese wood industry (Obataya et al 2006).…”
Section: Resultsmentioning
confidence: 67%
“…4), as measured by color indicator method described by AWPA (AWPA 1993). Longitudinal penetration is common for the passive impregnation method, as reported by earlier works 2009a,b;Ando et al 2012;. Preservative penetration on the longitudinal/radial surfaces was also greater than 93% at any depth that was cut, and the outer surfaces that were 0 and 12 cm from the laser-irradiating surface had higher penetration than the inner surfaces, which were 3, 6, and 9 cm from the surface.…”
Section: Preservative and Fire Retardant Retention And Penetrationmentioning
confidence: 66%
See 3 more Smart Citations